2015
DOI: 10.31254/phyto.2015.4307
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic tolerance study of hydro-alcoholic extract of Terminalia mantaly H. Perrier (Combretaceae) in rats

Abstract: Objective: The effect of the hydro-alcoholic extract of Terminalia mantaly H. Perrier (Combretaceae) was evaluated on liver tissue and biochemical markers in Rats were analyzed. Methods: The animals were divided into four groups of 10 animals each (5 males and 5 females). Group1 received 1 mL/100g body weight of distilled water and served as control. Groups 2, 3 and 4 received extract doses of 150,300 and 600 mg/kg body weight, respectively. Blood sampling was carried out to evaluate various biochemical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Thus, a first study was carried out to evaluate the hematological parameters and hepatic tolerance, renal tolerance. This study found that the hydroalcoholic extract of the plant could be well tolerated by rats, blood cells, liver and kidney [12] [13]. The present study aims to explore the effects of the hydroalcoholic extract of T. mantaly on certain biochemical markers of rats heart tissues.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, a first study was carried out to evaluate the hematological parameters and hepatic tolerance, renal tolerance. This study found that the hydroalcoholic extract of the plant could be well tolerated by rats, blood cells, liver and kidney [12] [13]. The present study aims to explore the effects of the hydroalcoholic extract of T. mantaly on certain biochemical markers of rats heart tissues.…”
Section: Introductionmentioning
confidence: 92%
“…Tumbuhan ini di Indonesia dimanfaatkan sebagai: (1) tumbuhan peneduh dengan tajuknya yang lebar berlapis-lapis, (2) penyerap polusi yang ada di lingkungan, dan (3) sebagai tanaman hias dalam bentuk mini ataupun pohon yang tumbuh tinggi mencapai belasan meter. Selain itu, di luar negeri, bagian tanaman ketapang kencana dimanfaatkan sebagai: (1) kulit kayunya yang mengandung tanin sebagai zat pewarna, (2) daun, batang, kulit akar digunakan secara etnomedis dalam pengobatan berbagai penyakit seperti: disentri, diabetes, gastroenteritis, kandidiasis mulut dan pencernaan (Tchuenmogne et al 2017), perawatan postpartum dan malaria (Emilie et al 2015).…”
Section: Jurnal Silvikultur Tropikaunclassified